Identification of Physiological and Pathological Patterns of Vertical Posture Regulation Using a Kohonen Neural Network with Stabilometry Data - Stepanyan, I. V.; Grokhovskii, S. S.; Yastrebtseva, I. P.; Kubryak, O. V. (Biomedical engineering, 2023)
A prospective study using force platform test results from 65 patients with loss of balance in the recovery period of ischemic cerebral stroke and 65 presumptively healthy subjects demonstrated that patterns of regulation of vertical posture in healthy individuals and patients with cerebral catastrophe could be roughly discriminated by analysis of the energy intensity of migrations of the trajectory of the common center of pressure on the support using a competitive self-organizing Kohonen neural network.